KAJIAN KUALITAS FISIKO KIMIA DAN MIKROBIOLOGI TEMPURA IKAN MUJAIR MENGGUNAKAN SODIUM TRIPOLYPHOSPHATE (quality assessment of microbiology, physical and chemical oftilapia fish tempura using sodium tripolyphosphate) (Jurnal Teknologi Pangan, 2015)
Abstract Tempura is one product of fish processing results. In Indonesia, the development of the tempura fish meatballs. Making tempura include: sorting, washing, peeling vegetables, ingredient mixing, making and frying. Problems tempura product is the save relatively short, therefore it needs the addition of compounds that act as antioxidants and antimicrobia in the tempura manufacture of Sodium Tripolyphosphate. The purpose of this research is to know the influence of addition of Sodium Tripolyphosphate and long term storage for the characterictic of chemicalphysic, organoleptic, microbiology and oreochromis mossambicus Tempura. The experimental design used was factorial Completely Random Design with two factors, namely the addition of Sodium Tripolyphosphate (0%; 0.25%; 0.50%) and during long term storage (0 days, 2 days, 4 days) with three replicates. The results showed that the best treatment is present on the oreochromis mossambicus tempura by the addition of Sodium Tripolyphosphate 0.50% and prolonged storage 4 days. oreochromis mossambicus Tempura has moisture content of 44,71%; WHC 45,41%; the texture of 0.21 mm/dt gr.; a total of 2,715 microbes log (cfu/g); peroxide number 5,68 (meq/1000 g); 4.14% fat content; Water activity (Aw) 0,77% with a value of organoleptic the smell of 116; the texture of the 125   Keyword : Oreochromis Mossambicus Tempura, sodium tripolyphosphate   Abstrak Tempura merupakan salah satu produk hasil pengolahan ikan. Di Indonesia, tempura merupakan pengembangan dari bakso ikan. Pembuatan tempura meliputi:sortasi, pencucian bahan, pengupasan sayuran, pencampuran, pencetakan dan pengorengan. Permasalahan pada produk tempura adalah masa simpan yang relatif pendek, oleh karena itu perlu penambahan senyawa yang berfungsi sebagai antioksidan dan antimikrobia dalam pembuatan tempura yaitu Sodium Tripolyphosphate. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh penambahan Sodium Tripolyphosphate dan lama penyimpanan terhadap sifat fisikokimia, mikrobiologi dan organoleptik Tempura ikan mujair. Rancangan percobaan yang digunakan adalah Rancangan Acak Lengkap (RAL) pola faktorial dengan 2 faktor yaitu penambahan Sodium Tripolyphosphate (0%;0,25%;0,50%) dan lama penyimpanan selama (0 hari,2 hari, 4 hari) dengan 3 kali ulangan.. Hasil penelitian menunjukkan bahwa perlakuan terbaik terdapat pada tempura ikan mujair dengan penambahan Sodium Tripolyphosphate 0,50% dan lama penyimpanan 4 hari. Tempura ikan mujair tersebut memiliki kadar air 44,71% ; WHC 45,41% ; tekstur 0,21 mm/gr.dt ; total mikroba 2,715 log(cfu/gr); angka peroksida 5,68 (meq/1000g) ; kadar lemak 4,14% ; Aktivitas air (Aw) 0,77% dengan nilai organoleptik bau 116 ; tekstur 125   Kata kunci : mujair, tempura, Sodium Tripolyphosphate